Uso de hidroterapia en caninos con displasia de cadera reporte de casos en un golden retriever y schnauzer miniatura: pasantía en la clínica animal welfare, Bogotá (2022)
In this report, we present the activities carried out during our time in an internship as a degree work modality, carried out at the Animal Veterinary Clinic Welfare, under the guidance of Dr. Nathalia Caballero, this clinic focuses on small animals (felines and canines), where we assist with veterinary consultations, customer service, veterinary emergencies and surgeries, the most prevalent being Ovariosalpingohysterectomy, and the most frequent clinical cases were Parvovirosis, which receive attention 24 hours a day, recognizing the importance of completing clinic history